German views on UNCTAD II - H. F. Schulz (Intereconomics, 1968)
Something about the immense importance of UNCTAD II can be inferred from the hypothetical assumption that the joint attempt of 132 nations to build a “world without poverty, misery, and despair” might founder, and from sober consideration of the effects of such an event. Numerous representatives of developing countries, in their introductory addresses to the Conference, have stressed the indispensable need for bridging the gap which separates the world into the two camps of the affluent and the poor, lest economic backwardness cause again and again major conflicts. We have discussed some aspects of UNCTAD II with Dr Schulz, the deputy acting head of the German deannation, shortly before he left Germany for New Delhi.
Keywords: 330; Interview